Prototype of an Automated Item Sorting System Using a Barcode Scanner and Servo-Based Directional Control with Microcontroller - syarif rizal julfanny (Universitas Kristen Immanuel, 2026)
The increasing demand for efficiency in logistics and manufacturing highlights the limitations of manual sorting systems, which are prone to errors and inefficiency under high-volume conditions. Existing automated sorting systems often rely on multiple sensors or complex configurations, resulting in higher costs and system complexity. This study aims to develop a cost-effective and simplified automated sorting prototype using a single barcode scanner integrated with servo-based directional control. The system is designed using an Arduino Mega 2560 microcontroller, GM66 barcode scanner, infrared sensors, DC conveyor motors, and MG996R servo motors. The proposed method involves object detection, barcode identification, data processing, and directional sorting based on predefined servo angles. Experimental results show that the system successfully performs automated sorting with an overall success rate of 50%, demonstrating functional feasibility despite mechanical limitations. It can be concluded that the proposed system offers a practical and economical solution for prototype-scale automated sorting applications.